The Adversus Arium of Marius Victorinus, The First Systematic Exposition of the Doctrine of the Trinity - Henry, Paul (The journal of theological studies, 1950)
Paul Henry; The Adversus Arium of Marius Victorinus, The First Systematic Exposition of the Doctrine of the Trinity1, The Journal of Theological Studies, Volume